Prevalence of dementia diagnoses not otherwise specified in eight European countries: a cross-sectional cohort study - Lethin C; Rahm Hallberg I; Renom Guiteras A; Verbeek H; Saks K; Stolt M; Zabalegui A; Soto-Martin M; Nilsson C. (My University, 2022)
Background
Dementia is a syndrome, with a wide range of symptoms. It is important to have a timely diagnosis during the disease course to reduce the risk of medication errors, enable future care planning for the patient and their relatives thereby optimizing quality of life (QoL). For this reason, it is important to avoid a diagnosis of dementia not otherwise specified (DNOS) and instead obtain a diagnosis that reflects the underlying pathology. The aim of this study was to investigate the prevalence and associated factors of DNOS in persons with dementia living at home or in a nursing home.
Methods
This is a cross-sectional cohort study performed in eight European countries. Persons with dementia aged ≥65 years living at home (n = 1223) or in a nursing home (n = 790) were included. Data were collected through personal interviews with questionnaires based on standardised instruments. Specific factors investigated were sociodemographic factors, cognitive function, and mental health, physical health, QoL, resource utilization and medication. Bivariate and backward stepwise multivariate regression analyses were performed.
Results
The prevalence of DNOS in the eight participating European countries was 16% (range 1–30%) in persons living at home and 21% (range 1–43%) in persons living in a nursing home. These people are more often older compared to those with a specific dementia diagnosis. In both persons living at home and persons living in a nursing home, DNOS was associated with more severe neuropsychiatric symptoms and less use of anti-dementia medication. In addition, persons with DNOS living at home had more symptoms of depression and less use of antidepressant medication.
Conclusions
The prevalence of DNOS diagnosis is common and seems to vary between European countries. People with DNOS are more often older with more severe neuropsychiatric symptoms and receive fewer anti-dementia medication, anxiolytics and antidepressants. This would support the suggestion that a proper and specific diagnosis of dementia could help the management of their disease.